Using the Technology Acceptance Model (TAM) to Measure the Impact of Chat GPT‘s Features as an AI Application on Behavioral Intentions: The Mediating Role of Egyptian Smartphone Users’ Satisfaction - Abdelaal, Elsayed (The Arab Journal of Administration, 2025)
Purpose: This study aims to identify the direct and indirect relationship effects of ChatGPT ‘s features on behavioral intentions through the mediating role of ChatGPT user satisfaction, considering user experience, age, and gender as control variables. Study Design/ Methodology/ Method: The study adopted the deductive approach and relied on descriptive and analytical research. The researcher used exploratory factor analysis and confirmatory factor analysis to reveal the dimensions/characteristics of the ChatGPT among Egyptian users. He also used simple and multiple regression analysis to test the significance of the impact of the ChatGPT ‘s characteristics on behavioral intentions and user satisfaction, and the impact of user satisfaction on behavioral intentions using SPSS.27, and path analysis using AMOS.24 to analyze the mediating role of user satisfaction in the relationship between ChatGPT characteristics and behavioral intentions. Sample and Data: A snowball sample of 335 Egyptian ChatGPT users to test four hypotheses. An online survey was used to collect this data. Results: According to the study sample of Egyptian users, the results indicated a significant positive effect of ChatGPT features on behavioral intentions and a partial significant effect of each of perceived social presence and perceived usefulness on the behavioral intentions of the Egyptian user. The effect of user experience was shown as a controlling variable in the relationship between ChatGPT features and behavioral intentions. There was also a significant positive effect of user satisfaction with the application on behavioral intentions, and an effect of the ChatGPT features represented by (perceived social presence, perceived usefulness, and perceived ease of use) on Egyptian user satisfaction. There was also a partial significant effect of the perceived usefulness of using ChatGPT on user satisfaction, in addition to a significant indirect positive effect of the ChatGPT features on behavioral intentions when mediating Egyptian user satisfaction. It was also shown that there was a partially significant positive effect of perceived usefulness on behavioral intentions to adopt the chatbot when mediating user satisfaction. Research Limitations / Implications: The study was limited to Egyptian users of ChatGPT and relied on a non-probability sample.